THE APPLICATION OF YOUTUBE MEDIA IN DEMONSTRATION METHODS TO IMPROVE PRAYER IMPLEMENTATION SKILLS - Zhilal, Marhamah; Thaib, Muhammad Ichsan (Al-Mubin, 2025)
The background of the research shows that most students struggle to understand and correctly perform the procedures of Islamic prayer due to the limitations of conventional teaching methods. This study aims to improve students’ prayer performance skills through the application of YouTube media in the demonstration method. This research employed a Classroom Action Research (CAR) approach conducted in two cycles. Data were collected through observations of teacher and student activities, as well as assessments of student engagement. The results revealed a significant improvement in teacher activity, student involvement, and student participation during the learning process. The average student engagement increased from 75.76% in the first cycle to 88.25% in the second cycle, while teacher activity rose from 82.35% to 88.2%. Therefore, the use of YouTube media in the demonstration method has proven to be effective in enhancing students’ prayer performance skills